2000
DOI: 10.1212/wnl.54.3.679
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of t-PA in acute ischemic stroke

Abstract: The use of t-PA for stroke in this community is effective with a number needed to treat of six. The risk of symptomatic hemorrhage is similar to that noted in randomized trials. Treating patients who violate protocol results in excess risk with no observable benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 38 publications
8
68
2
2
Order By: Relevance
“…The door to needle times for our patients are comparable to those reported in other series, 2,4,10,19 and those for patients transferred from rural hospitals were within the 1 hour recommended by guidelines. 20 This was significantly shorter than times for patients who presented directly to a London hospital.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The door to needle times for our patients are comparable to those reported in other series, 2,4,10,19 and those for patients transferred from rural hospitals were within the 1 hour recommended by guidelines. 20 This was significantly shorter than times for patients who presented directly to a London hospital.…”
Section: Discussionsupporting
confidence: 89%
“…The outcomes in our patients are comparable with those of the NINDS trial, 1 and they contribute to the growing number of studies that have demonstrated the safety and effectiveness of tPA when used in routine clinical practice. 2,4,5,10,19 Given the geographic location of London, the demographic characteristics of southwestern Ontario, and the fiscal constraints of the Canadian health system, our stroke team must provide stroke care coverage to a large geographical area. Other centers have reported successes with the use of tPA in rural settings or in settings where access to neurologists and imaging facilities is limited.…”
Section: Discussionmentioning
confidence: 99%
“…3), and was similar to rates in other reported series. [26][27][28][29][30][31][32][33][34][35][36] Serious adverse events occurred in 75 (6.6%) of the patients (95% CI 5.2%-8.2%) ( Table 3). Of the 52 (4.6%) who had a symptomatic intracranial hemorrhage, 39 (75%) died in hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Con respecto al segundo caso clínico, el uso de rt-PA para fibrinólisis en casos de ACV isqué-micos agudos tiene una efectividad conocida en cuanto a recuperar la independencia del paciente y un margen de seguridad aceptable si se realiza según protocolos establecidos 14,15 . La evolución clínica favorable y la disolución del trombo en este paciente con un tratamiento médico (y no quirúrgico como en el primer caso) demostraron que la decisión de iniciar heparina fue la adecuada.…”
Section: Discussionunclassified